Security that Matters: General Knowledge and Correlations in the Context of Applied Satellite Navigation, Specific Interference-Events and the Use of the GNSS-Technology (European Journal of Social Sciences, 2022)
Navigation through global navigation satellite systems (GNSS) has become an indispensable part of modern life with threats such as GNSS interference, making it necessary to uncover relevant psychological aspects in the context of the GNSS construct, diverse interference events, and the use of related technologies. A total of n = 122 subjects participated in an online survey, which included scales and specifically constructed items on GNSS usage, acceptance, dependence, and self-assessed sense of direction and relevance of basic psychological needs. In addition, frequently emphasized factors influencing acceptance and use of diverse technologies were recorded according to the Unified Theory of Acceptance and Use of Technology (UTAUT; Venkatesh et al., 2003). Correlation analyses showed that the frequency of GNSS use was associated with both effort expectation of appropriate technologies, hedonistic motivation, habits of using GNSS-enabled devices, and specific aspects of mobility. In terms of reported GNSS dependency, negative correlations were found with self-assessed orientation ability. It was also possible to identify voluntariness in the use of related technologies, the age of the users, and the relevance of self-determination as essential variables in the context of GNSS use. The results underline the need for further investigation of psychological aspects and contribute to existing discussions in the context of various threat scenarios.